Kafa'ah in The Muslim Community Marriage : a Study of The Social History of Islamic Law - Abdul Hadi Ismail (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
Kafa'ah is a tradition that existed in the Aran Peninsula long before the arrival of Islam. This means that the kafa'ah which later became an interesting discussion in the social history of Muslims to this day is not without strong historical roots. Kafa'ah is a method for finding a prospective husband or wife in an equal measure. Before Islam came, then the standard of the kafa'ah was one's nasab, but when Islam came, the measure was religion or religious observance. Kafa'ah, which was born from a culture in a particular society, has also different characteristics, depending on where the community is located and other factors that are around the community. Therefore, in the present context, kafa'ah between a certain tribe or a community is not the same size.